Quantitative Extraction and Evaluation of Tomato Fruit Phenotypes Based on Image Recognition - Zhu, Yihang; Gu, Qing; Zhao, Yiying; Wan, Hongjian; Wang, Rongqing; Zhang, Xiaobin; Cheng, Yuan (Frontiers in Plant Science, 2022)
Tomato fruit phenotypes are important agronomic traits in tomato breeding as reference index. The traditional measurement methods based on manual observation, however, limit the high-throughput data collection of tomato fruit morphologies. In this study, fruits of ten different tomato cultivars with considerable differences in fruit color, size and other morphological characters were selected as samples. Constant illumination condition was applied to take images of the selected tomato fruit samples. Based on image recognition, automated methods for measuring color and size indicators of tomato fruit phenotypes was proposed. A deep learning model based on Mask R-CNN (Region-Convolutional Neural Network) was trained and tested to analyze the internal structure indicators of tomato fruit. The results revealed that the combination use of these methods can extract various important fruit phenotypes of tomato, including fruit color, horizontal and vertical diameters, top and navel angles, locule number, pericarp thickness etc. automatically. Considering several corrections of missing and wrong segmentation cases in practice, the average precision of the deep learning model is more than 0.95 in practice. This suggests a promising locule segmentation and counting performance. Vertical/horizontal ratio (fruit shape index) and locule area proportion were also calculated based on the data collected here. The measurement precision was comparable to manual operation, and the measurement efficiency was highly improved. The results of this study will provide a new option for more accurate and efficient tomato fruit phenotyping, which can effectively avoid artificial error and increase the support efficiency of relevant data in the future breeding work of tomato and other fruit crops.